Delft: Views on Delft - Staničić, Aleksandar; Tanis, Fatma; Sioli, Angeliki; Havik, Klaske; Dale, Holly; Vogel, Willie; de Wit, Saskia; Mejía Hernández, Jorge; Perez Guembe, Elena; Pllumbi, Dorina; et al. (Writingplace, 2023)
Around 1661, Johannes Vermeer painted what has become one of the most famous city views: the View of Delft. Delft, an intermediate European city in the Netherlands, located between The Hague and Rotterdam, has featured quite prominently in Dutch city narratives, partially thanks to Vermeer’s paintings, which showed fragments of both spatial and social characteristics of the city in the seventeenth century. As Delft is the city where this Writing Urban Place network originated, and where many members of the network have lived, studied or lectured, or are still doing all the above, this contribution collects their views on Delft, painting for our readers, in words, their accounts of the sociospatial characteristics of this city, their relationship with the water, their favourite urban places, their personal views of Delft.